2008
DOI: 10.3402/ljm.v3i3.4775
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Variation of Sphenoid Sinus and Related Structures in Libyan Population: CT Scan Study

Abstract: BackgroundSphenoid sinus is the most inaccessible paranasal sinus, enclosed within the sphenoid bone and intimately related to numerous vital neural and vascular structures. Anatomic variation of the sphenoid sinus is well documented and may complicate surgery in such a place.ObjectiveTo outline the surgically risky anatomic variants of the sphenoid sinus as well as the variable relationships between the sinus and related neurovascular structures, for the safe removal of intrasphenoid and pituitary lesions.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
107
5
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 29 publications
9
107
5
2
Order By: Relevance
“…the small space on the lateral wall of the sphenoid sinus, between the optic canal, supe-riorly, and the carotid prominence, inferiorly. The opticocarotid recess is presumed to concur with ipsilateral optic nerve protrusion into the sphenoid sinus 8 . Sirikci et al 1 , Ünal et al 4 and Hewaidi et al 8 reported a significant relationship between protrusion of the ON into SS and the pneumatization of ACP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the small space on the lateral wall of the sphenoid sinus, between the optic canal, supe-riorly, and the carotid prominence, inferiorly. The opticocarotid recess is presumed to concur with ipsilateral optic nerve protrusion into the sphenoid sinus 8 . Sirikci et al 1 , Ünal et al 4 and Hewaidi et al 8 reported a significant relationship between protrusion of the ON into SS and the pneumatization of ACP.…”
Section: Discussionmentioning
confidence: 99%
“…The opticocarotid recess is presumed to concur with ipsilateral optic nerve protrusion into the sphenoid sinus 8 . Sirikci et al 1 , Ünal et al 4 and Hewaidi et al 8 reported a significant relationship between protrusion of the ON into SS and the pneumatization of ACP. We observed 23.5 % patients on the right side and 14.7 % patients on the left side with both pneumatization of ACP and protrusion of ON.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the ICA bulging (Figure 10) into the sphenoid sinus varies from 3 to 41% [15,[47][48][49][50][51]. In case of bulging, an ICA injury may occur due to a trauma or a complication of sinus disease.…”
Section: Sphenoid Sinus Ica and Mn Relationsmentioning
confidence: 99%
“…In case of bulging, an ICA injury may occur due to a trauma or a complication of sinus disease. If the surgeon is not aware of this variation, fatal haemorrhage can occur; it is Paranasal Sinuseshardly possible to control the bleeding from this artery, and neurological sequelae are inevitable [15,51]. Another complication during the surgery is if the septum in the sphenoid sinus (Figure 11) adheres to the wall of the ICA, the surgeon must be careful about not fracturing it to avoid the artery damage [18,50].…”
Section: Sphenoid Sinus Ica and Mn Relationsmentioning
confidence: 99%
See 1 more Smart Citation